The giant Kalgoorlie Gold Field revisited - Vielreicher, N.; Groves, D.; McNaughton, Neal (2015)
© 2015 China University of Geosciences (Beijing) and Peking University. The Neoarchaean Kalgoorlie Gold Field contains the giant Golden Mile and world-class Mt Charlotte deposits, which have been the subject of much research for over 100 years. The Golden Mile deposit is a complex array of ductile to brittle vein and breccia lodes that are predominantly hosted in the highly-fractionated Golden Mile Dolerite sill. The Fimiston lodes comprise an array of narrow lodes that evolved broadly syn- to late-formation of the regional D2 NW-trending foliation. The lodes are characterized by pyrite veinlets and disseminations, quartz veinlets and breccias, and banded quartz-carbonate veins with sericite, carbonate, and pyrite-dominated alteration. Bonanza Green-Leader, or Oroya-style, lodes, with grades in excess of 1000 g/t Au, are similar to the Fimiston-style lodes, but are characterized by abundant visible gold, native tellurium and more abundant telluride minerals within roscoelite-bearing alteration zones. The arguably structurally younger Mt Charlotte-style lodes are characterized by a pipe-shaped, coarse-grained quartz, carbonate and scheelite vein-stockwork with distinct vertically-zoned, carbonate-sericite-albite-pyrite ± pyrrhotite dominant alteration assemblages around veins within Unit 8 of the Golden Mile dolerite and porphyry dykes. The network of steep- and gently-dipping extension and shear fracture-fill veins are associated with NE-trending fault sets that cross cut the regional NW-trend. The deposit area is intruded by swarms of porphyry dykes, including syn-volcanic mafic dykes, early and volumetrically most significant c. 2.67 Ga feldspar-phyric porphyry dykes, as well as later c. 2.66-2.65 Ga calc-alkaline hornblende-phyric dykes associated with younger c. 2.65-2.64 Ga lamprophyre dykes. All post-volcanic dykes have similar orientations to the Fimiston lodes. The feldspar dykes are clearly overprinted by all styles of mineralization, although the relationship between hornblende-phyric and lamprophyre dykes and gold mineralization is more ambiguous. Most agree that gold mineralization was post-peak regional metamorphism of host rocks, although its relative structural timing is controversial.Direct timing constraints on gold mineralization indicate that Fimiston- and Mt Charlotte-style mineralization formed within a relative short period of time around 2.64 Ga, and, as such, support a model of progressive deformation of a rheologically heterogeneous rock package late in the structural history. Fluid characteristics, combined with the structural, metamorphic and absolute timing, support description of gold mineralization at the Golden Mile as orogenic and mesozonal, and this allows direct correlation with orogenic gold deposits worldwide, which classically formed during accretion along convergent margins throughout Earth history.